STIGMA SOSIAL DALAM FILM TILIK (Analisis Tiga Tataran Semiotika Tzvetan Todorov) - Elu, Stefanus Poto; Sukmaranti, Galuh (FISIP Universitas Bung Karno, 2023)
AbstractFilm is art, as well as a medium for conveying messages to society. The themes of films are generally based on social issues that exist in society. In Indonesia, we know two types of film, namely long films and short films. If long films require a long time to make, then short films are generally shorter. Short film story ideas are usually taken from everyday stories. In this way, the message of the short film is easily digested by the audience. The short film TILIK, which was released in 2018, was then shown to the wider public via the YouTube channel in 2020, successfully attracting the attention of Indonesian short film viewers. This is what attracted researchers' interest in elaborating on this short film. The theory used in this research is Tzvetan Todorov's semiotic theory. Through Todorov's theory, researchers want to elaborate on the construction of social stigma contained in the short film TILIK. By using qualitative descriptive methods, researchers found that this film is full of social stigma that lives in society. Information on the internet and social media correlatively enlivens social stigma towards certain figures. Moreover, if it is not accompanied by adequate literacy skills, everyone will become a producer and consumer of hoax news in society, the internet and social media. Keywords: Semiotics, Tzvetan Todorov, Short film, Tilik